Pengaruh Komunikasi Organisasi, Loyalitas Ustaz dan Iklim Organisasi terhadap Produktivitas Kerja Pondok Pesantren di Kabupaten Bireuen - Azhari, Azhari; Sulaiman, Tengku; Konadi, Win (peusangan, 2023)
Based on the phenomenon of the condition of Islamic boarding schools in Bireuen Regency, both of which provide formal and non-formal education, researchers are interested in seeing and further examining the condition of Islamic boarding schools’ work productivity by trying to analyze it. from the influence of Organizational Communication Patterns, Ustaz Loyalty and Organizational Climate at Islamic Boarding Schools in Bireuen Regency. By taking a sample of ustadz in 17 sub-districts that manage Islamic boarding schools in implementing formal and non-formal education. Quantitative analysis with path analysis approach. The results showed that there was a partial positive effect on interpersonal communication, ustadz loyalty and organizational climate on ustadz work productivity, and (2) simultaneously obtained the contribution of interpersonal communication factors, ustadz loyalty and organizational climate on ustadz productivity at Islamic boarding schools. Bireuen Regency by 61.4%.